Transmission of Chromosomal MDR DNA Fragment Encoding Ciprofloxacin Resistance by a Conjugative Helper Plasmid in Salmonella - Yang, Chen; Chen, Kaichao; Chan, Edward Wai-Chi; Yao, Wen; Chen, Sheng (Frontiers in Microbiology, 2020)
Resistance to ciprofloxacin, a treatment choice for Salmonella infections, has increased dramatically in recent years in particular in serotype Salmonella Derby with most of strains carrying chromosome-encoded multiple plasmid-mediated quinolone resistance (PMQR) genes. In this work, we discovered a conjugative plasmid, pSa64-96kb, in a Salmonella Derby isolate, namely Sa64, which could extract and fuse to a multiple drug resistance (MDR) DNA fragment containing two PMQR genes, aac(6’)-Ib-cr, and qnrS2 located on the chromosome of the Salmonella strain. This process led to the formation of a new 188 kb fusion plasmid, which could be then subsequently transmitted to recipient strain Escherichia coli J53. The chromosomal MDR DNA fragment was shown to be flanked by one copy of IS26 element at each end and could be excised from the chromosome to form circular intermediate, which was then fused to pSa64-96kb and form a single plasmid through IS26 mediated homologous recombination. The role of IS26 on enhancing the efficacy of fusion and transmission of this chromosomal MDR DNA fragment was further proven in other Salmonella strains. These findings showed that dynamic interaction between specific chromosomal fragment and plasmids may significantly enhance resistance development and transferability of mobile resistance-encoding elements among bacterial pathogens.